2010
DOI: 10.1186/1477-7827-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of both gene expression and activity of Hsp27 improved maturation of mouse oocyte in vitro

Abstract: BackgroundHeat shock protein 27 (Hsp27), a member of the small heat shock protein family, is an apoptosis regulator. Our previous proteomic study showed that Hsp27 mainly expressed in human oocyte, and that Hsp27 expression was downregulated in the ovaries derived from women with the polycystic ovary syndrome (PCOS), a well known endocrinal disorder with abnormal apoptotic activity and folliculogenesis. However, the exact effects of Hsp27 downregulation on oocyte development have not yet been clarified.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 73 publications
5
10
0
Order By: Relevance
“…which is consistent with our previous study [15]. Interestingly, Results of the present study also showed that overexpression of Hsp27 didn't affect the rate of fertilization, and even enhanced the embryonic developmental potential of PCOS oocytes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…which is consistent with our previous study [15]. Interestingly, Results of the present study also showed that overexpression of Hsp27 didn't affect the rate of fertilization, and even enhanced the embryonic developmental potential of PCOS oocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous work demonstrated that upregulation of apoptotic-related factors Caspase 8 and Caspase 3 could increase the early apoptotic rate of oocytes, and promoted oocyte maturation in mouse oocytes. Contrastingly, the overexpression of Hsp27 in oocytes was shown to downregulate Caspase 8 and Caspase 3 expression, which depressed the early stages of apoptosis [15]. These findings were further supported by our observation that upregulated Hsp27 expression had an inhibitory effect on oocyte maturation in PCOS patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Over-expression of Hsp27 in oocytes derived from PCOS patients leads to inhibition of oocyte maturation, but improves embryonic developmental potential by down-regulating oocyte-secreted factors, BMP15 and GDF9, and the apoptoticrelated regulators, Caspase 3, 8 and 9 [353]. Downregulation of Hsp25 improved the maturation of mouse oocytes but increased early stage of apoptosis through the activation of extrinsic, caspase 8-mediated pathway [354]. Though the exact mechanism of these observations still needs to be explored, it appears that Hsp27/Hsp25 critically regulates oocyte maturation and its developmental potential through regulation of apoptosis as one of the mechanisms.…”
Section: Shsps In Fertilization and Developmentmentioning
confidence: 96%
“…In this sense, in oocytes HSPB1 targeting promoted caspase-3 activation in the absence of caspase-9 activation, similar to the observation in podocytes exposed to high-glucose conditions. 52 Podocyte injury results in proteinuric renal disease. 53 Contrary to MCD, both DN and FSGS are progressive glomerular diseases characterized by progressive loss of podocytes in which podocyte apoptosis has been observed.…”
Section: Discussionmentioning
confidence: 99%